Conservation of an isolated and genetically unique population: red squirrels on the Isle of Wight - Alyson E.V. Buchanan; Demetra Andreou; Kathy H. Hodder; Melissa A. Toups; Phillipa K. Gillingham; Marin Cvitanović; Helen Butler; Emilie A. Hardouin (Biodiversity and Conservation, 2025)
Island populations face a higher extinction risk than mainland ones due to their smaller population sizes, limited genetic diversity, and increased vulnerability to environmental changes and stochastic events. The Isle of Wight red squirrel population is culturally and economically significant, being the largest remaining population in Southern England and genetically distinct from European populations. We used a multidisciplinary approach to assess the population’s long-term viability, evaluating habitat and food resources, analysing microsatellite genetic data, and using life history data to model population viability. Results indicated that natural food resources, supplemented by additional feeding, could sustain and support population growth. Microsatellite data identified two genetic clusters in the east and west of the island. Although F ST values were non-significant, indicating gene flow between subpopulations, elevated F IS values suggest localised mating dynamics driven by limited dispersal and spatial structure rather than systemic inbreeding. Population viability analyses suggested that habitat fragmentation and localised inbreeding do not pose immediate threats. However, maintaining connectivity between subpopulations remains crucial to preserving genetic diversity and reducing future risks of genetic isolation or increased inbreeding. Under pessimistic scenarios with reduced survival rates and fewer litters, model predictions indicated population decline and increased extinction risks. Future research should incorporate fine-scale spatial genetic analyses using genome data to explore population structure, local adaptation, and differentiate local mating dynamics from population-wide inbreeding. While direct data on inbreeding, litter sizes, and survival rates are challenging to obtain, these insights are critical for understanding population dynamics and guiding conservation efforts.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Wildlife conservation in a fragmented landscape: the Eurasian red squirrel on the Isle of Wight - Emilie A. Hardouin; Helen Butler; Marin Cvitanović; Rainer G. Ulrich; Vanessa Schulze; Anna-Katarina Schilling; Peter W. W. Lurz; Anna Meredith; Kathy H. Hodder (Conservation Genetics, 2021)
Island populations may have a higher extinction risk due to reduced genetic diversity and need to be managed effectively in order to reduce the risk of biodiversity loss. The Eurasian red squirrels ( Sciurus vulgaris ) in the south of England only survive on three islands (the Isle of Wight, Brownsea and Furzey islands), with the Isle of Wight harbouring the largest population in the region. Fourteen microsatellites were used to determine the genetic structure of red squirrel populations on the Isle of Wight, as well as their relatedness to other populations of the species. Our results demonstrated that squirrels on these islands were less genetically diverse than those in Continental mainland populations, as would be expected. It also confirmed previous results from mitochondrial DNA which indicated that the squirrels on the Isle of Wight were relatively closely related to Brownsea island squirrels in the south of England. Importantly, our findings showed that genetic mixing between squirrels in the east and west of the Isle of Wight was very limited. Given the potential deleterious effects of small population size on genetic health, landscape management to encourage dispersal of squirrels between these populations should be a priority.

Techniques for evaluating the spatial behaviour of river fish - Kathy H. Hodder; Jerome E. G. Masters; William R. C. Beaumont; Rodolphe E. Gozlan; Adrian C. Pinder; Carolyn M. Knight; Robert E. Kenward (Hydrobiologia, 2007)